Counterfeiting in China: A Great Challenge in Intellectual Property Protection - Lusita, Lusita (UI Scholars Hub, 2012)
Counterfeiting is an increasing problem for Intellectual Property Rights (“IPR”) protection throughout the world. Counterfeiting activities are generally related to trademark infringements as the counterfeiters are trying to generate instant benefits from the established trademarks around the world by using such marks without consent. Counterfeit products manufactured in People’s Republic of China (“PRC”) might be considered as the greatest evidence of IPR law contravention. The national government has not been successful in decreasing the large number of counterfeiting cases. Therefore, in this article, the counterfeiting in the PRC will be examined initially in order to verify the fundamental concerns and the significantly influential factors in combating counterfeiting. Possible solutions are suggested and considered along with the other issues so that counterfeiting problems may gradually be reduced within the country.